RESEARCH ON THE LEVEL OF PROFESSIONAL BURNOUT OF THE EMPLOYEES OF THE OUTPATIENT HEALTH CENTRE "X" THE FACTORS INFLUENCING IT, AND DEVELOPMENT OF RECOMMENDATIONS FOR BURNOUT MANAGEMENT IN THE WORK ENVIRONMENT - Feofilova, Anastasija; Kurmeļeva, Alīna; Dubiņina, Evita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
Over the past three years, the COVID-19 pandemic caused medical congestion and increased the incidence of burnout among medical professionals. In Europe, about a third of medical professionals experienced burnout. The aim of the study is to investigate the burnout rate of the staff of the outpatient health centre “X” and to develop recommendations for reducing burnout in the work environment. Methods used were scientific literature analysis, interview of the heads of the structural units of the observed outpatient centre, Maslach Burnout Inventory, qualitative data analysis, and quantitative data analysis. The research took place in Riga in spring 2022. The study results showed that the average burnout level in this outpatient centre is middle level. The most suffer from burnout functional specialists.